Study of the propagation of an intense ion beam to the target; Vacuum; Vol. 198 - Stepanov A. V. Andrey Vladimirovich; Zhong Haowen; Zhang Shijian; Xu Mofei; Le Xiaoyun; Remnev G. E. Gennady Efimovich (2022, 2022)
Title screen